Role of Homoeopathy in Treatment of Irritable Bowel Syndrome - A Case Report (Advancements in Homeopathic Research, 2023)
Irritable Bowel Syndrome (IBS) is a recurrent  chronic disorder of gasterointestinal system affecting  10-30% of total worldwide population. Women are  more affected than men. Homoeopathy is one of the  system of medicine which acts on psychosomatic  plane of an individual which can bring IBS to  complete cure. Homeopathy is the choice of  treatment for all psychosomatic disorders especially  for IBS. Management of IBS should concentrate on  psychological and behavioral interventions along  with proper medication. Reducing mental stress,  regular exercises, yoga and meditation will give  more beneficial in reducing the severity of IBS.
Keywords: Irritable Bowel Syndrome; Homeopathy; Gastero intestinal disorders; Rome IV criteria